2019
DOI: 10.12659/msm.915005
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Protects Against Cerebral Aneurysmal Degenerative Pathology by Promoting Endothelial Progenitor Cells (EPC) Mobilization and Attenuating Vascular Deterioration in a Rat Model

Abstract: Background Endothelial injury is the early pathological change of cerebral aneurysm (CA) formation. In addition to its lipid-lowering activity, atorvastatin (ATR) also reportedly promotes vascular repair via mobilizing endothelial progenitor cells (EPC). Here, we investigated the influence of ATR on vascular worsening after CA induction in rats. Material/Methods Adult male Sprague-Dawley rats were randomly assigned to 3 groups: a control (CTR) group, a CA group, and a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Concurrently elevating the prevalence of endothelial cells and SMCs, as well as downregulating the expression and activity of metalloproteinase-2 and metalloproteinase-9, forestalls damage to and remodeling of the aneurysm wall. Similarly, rosuvastatin can enhance endothelialization at the aneurysm neck in a rat embolization model [96,97], augment the number of endothelial progenitor cells (EPCs), and restrict inflammation of the vascular wall. These findings suggested that statins could confer protection to or facilitate the repair of the aneurysm wall via a multitude of mechanisms, forestalling its expansion and rupture.…”
Section: Lipid Metabolism Disorder As a Therapeutic Target For Iamentioning
confidence: 99%
“…Concurrently elevating the prevalence of endothelial cells and SMCs, as well as downregulating the expression and activity of metalloproteinase-2 and metalloproteinase-9, forestalls damage to and remodeling of the aneurysm wall. Similarly, rosuvastatin can enhance endothelialization at the aneurysm neck in a rat embolization model [96,97], augment the number of endothelial progenitor cells (EPCs), and restrict inflammation of the vascular wall. These findings suggested that statins could confer protection to or facilitate the repair of the aneurysm wall via a multitude of mechanisms, forestalling its expansion and rupture.…”
Section: Lipid Metabolism Disorder As a Therapeutic Target For Iamentioning
confidence: 99%
“…However, the effects of statins on IAs are controversial. Some statins, such as atorvastatin [ 89 ], simvastatin [ 90 ], pitavastatin [ 91 ], and pravastatin [ 92 ] showed protective effects in animal IA models. In contrast, statins have been reported to promote the growth of experimentally-induced IAs in estrogen-deficient rats, although a low dose of pravastatin does reduce the incidence of IA [ 93 ], suggesting a possibility of differential effects by statins, particularly in older female patients with low estrogen levels.…”
Section: Ho-1 In Intracranial Aneurysmmentioning
confidence: 99%